2007
DOI: 10.1111/j.1365-2036.2006.03185.x
|View full text |Cite
|
Sign up to set email alerts
|

Gastro‐oesophageal reflux disease in chronic laryngitis: prevalence and response to acid‐suppressive therapy

Abstract: SUMMARY BackgroundGastro-oesophageal reflux is thought to cause chronic laryngitis through laryngopharyngeal reflux. Response of laryngitis to treatment with acid-suppressive therapy supports this causal link.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
54
1
3

Year Published

2008
2008
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(63 citation statements)
references
References 33 publications
3
54
1
3
Order By: Relevance
“…The causal association between acid reflux and laryngitis is highly plausible considering the close anatomical relationship. The vagally mediated reflexes (bronchospasm, laryngospasm and cough) stimulated by esophageal acid is also implicated in the pathogenesis of GERD-related extra-esophageal disorder [11,15] . Currently, there is no "gold-standard" for the diagnosis of LPR.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The causal association between acid reflux and laryngitis is highly plausible considering the close anatomical relationship. The vagally mediated reflexes (bronchospasm, laryngospasm and cough) stimulated by esophageal acid is also implicated in the pathogenesis of GERD-related extra-esophageal disorder [11,15] . Currently, there is no "gold-standard" for the diagnosis of LPR.…”
Section: Discussionmentioning
confidence: 99%
“…Patients were excluded from the study if they had a history of respiratory or gastrointestinal malignancy; radiation therapy to the head and neck, lung, or gastrointestinal tract; gastroesophageal surgery; use of H 2 -receptor antagonists or proton pump inhibitors in previous 1 mo; past or present smoker; excessive alcohol consumption; chronic cough attributable to known chronic pulmonary or tracheobronchial disease; professional voice users (e.g. singer, teacher); excessive voice use; exposure to occupational or environmental pollutants; history of seasonal allergic rhinitis; pharyngolaryngeal infection in the previous 3 mo; tracheal intubation in the previous 12 mo and use of inhaled corticosteroids [10,11] .…”
Section: Recruitment Of Patientsmentioning
confidence: 99%
“…The association between gastroesophageal reflux disease (GERD) and laryngopharyngeal reflux (LPR) is well established, and extra-esophageal symptoms, eg, hoarseness and globus sensation, improve with acid suppression. 4 A systematic review found an increased risk of chronic cough in patients with GERD (odds ratio, 1.7; 95% CI, 1.4 -2.1), 5 and a national cross-sectional postal survey in Scotland found a 31% prevalence of sore throat.…”
mentioning
confidence: 99%
“…Various modifi cations of the Laryngeal Symptom Score (LSS) have been used in some studies (Williams et al 2004;Wo et al 2006;Qua et al 2007). The frequency and severity of a number (usually up to 6) of LPR symptoms are assessed over the preceding week to give a cumulative score.…”
Section: Patient Reported Outcomes In Laryngopharyngeal Refl Uxmentioning
confidence: 99%